The failure of radical treatments to cure cancer: can less deliver more? - Angus G. Dalgleish; Peter L. Stern (SAGE Publishing, 2018)
All too often attempts to deliver improved cancer cure rates by increasing the dose of a particular treatment are not successful enough to justify the accompanying increase in toxicity and reduction in quality of life suffered by a significant number of patients. In part, this drive for using higher levels of treatment derives from the nature of the process for testing and incorporation of new protocols. Indeed, new treatment regimens must now consider the key role of immunity in cancer control, a component that has been largely ignored until very recently. The recognition that some drugs developed for cytotoxicity at higher doses can display alternative anticancer activities at lower doses including through modulation of immune responses is prompting a significant re-evaluation of treatment protocol development. Given that tumours are remarkably heterogeneous and with inherent genetic instability it is probably only the adaptive immune response with its flexibility and extensive repertoire that can rise to the challenge of effecting significant control and ultimately elimination of a patient's cancer. This article discusses some of the elements that have limited higher levels of treatment outcomes and where too much proved less effective. We explore observations that less can often be as effective, if not more effective especially with some chemotherapy regimens, and discuss how this can be exploited in combination with immunotherapies to deliver nontoxic improved tumour responses.